European Union Litigation - Philipp Hacker; Marie-Sophie Schäfer (European Review of Contract Law (ERCL), 2018)
This article provides an overview of cases decided by the Court of Justice of the European Union concerning contract law. The present issue covers the period between July 2017 and the beginning of January 2018.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; EU; European Court of Justice; lawsuit; law of obligations; consumer protection; labor law; court decision